Theoretical prediction of pKa for amino acids and voltammetric behaviour of the interaction of paracetamol with alanine - Khalis Mohammed Shahadha, Ammar Abdulsattar Ibrahim (International Journal of Advanced Science and Technology, 2020)
The interaction of paracetamol medicine with alanine has been investigated using electrochemical and quantum calculations. Square wave voltammetry (SWV) was applied to study the phenomena of this interaction at phosphate buffer solution as supporting electrolyte at pH=7. The peak of alanine was measured (Ep= 0.310 V) at solid electrode (platinum). The calibration curve of alanine give two step an excellent correlation coefficient (R2=0.943 and R2=0.961). The quantum physical parameters of the amino acids and the interaction of alanine compounds with paracetamol were evaluated using theoretical calculations by Hartree Fock at basis set (STO-3G). Also, pKa values were predicted depending on the parameters which determined theoretically. Key words: Paracetamol, Alanine, HOMO, LUMO, Square wave voltammetry, pKa